Birth in Prison: Systemic Discrimination Barriers to Acknowledging the Legal Personhood of the Child - Hansen, Robin F. (Columbia Journal of Gender and Law, 2025)
This Article uses systems theory to outline the problem of automatic rights denial of children born to incarcerated persons. Despite the demonstrated health importance of bonding in early infancy, children are routinely separated from their mothers at birth without due process or consideration of their interests. While this separation is enacted by corrections administrators, it is in fact conduct sent into motion by the earlier decision to incarcerate a pregnant person, even in the knowledge that this will mean automatic separation of the child and mother at birth. This Article argues that such incarceration decisions are communicating a devalued understanding of the pregnant person, labeling her as a worthless mother to her child. By identifying and rejecting discriminatory norms in legal system communications, the rights of children can be better projected.